PENGARUH CAPITAL ADEQUACY RATIO (CAR) , LOAN TO DEPOSIT RATIO (LDR), DAN NON-PERFORMING LOAN (NPL) TERHADAP PROFITABILITAS BANK UMUM YANG TERDATA DI BEI - Stefanus Vander Filipus Situmorang; Salsabillah Sofyanni; Tantri Octora Dwi Syah Putri; Zuwina Miraza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine how the profitability of commercial banks listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period is influenced by Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Non-Performing Loans (NPL). The importance of profitability as an indicator of bank soundness in managing economic risks, particularly following financial credit relaxation policies, serves as the background of this research. Financial ratio theory and banking management are employed to assess operational effectiveness. Using purposive sampling combined with a descriptive quantitative research approach, this study selected six banks as samples with a total of thirty observations. Secondary data were collected through documentation and literature review from official annual financial reports. The data were analyzed using multiple linear regression and classical assumption tests with SPSS software. The results show that CAR, LDR, and NPL simultaneously have a significant effect on Return on Assets (ROA). Partially, CAR has a positive and significant effect on ROA, while NPL has a significant negative effect. In contrast, LDR does not have a significant effect on profitability in this model. The Adjusted R Square value of 0.695 indicates that the independent variables explain 69.5% of the variation in profitability. Strengthening capital and controlling non-performing loans are essential to maintaining bank financial performance.